The Role of Spiritual Leadership, Perceived Organizational Support, Affective Commitment in Enhancing Organizational Citizenship Behavior - Erliani, Sri; Ramadhani, Sri Ridma; Noor, Syufian; Saputra, Adisurya (Jurnal Ilmiah Sumber Daya Manusia, 2025)
Organizational Citizenship Behavior (OCB) refers to employees' voluntary actions beyond formal job descriptions that positively contribute to organizational effectiveness. This study aims to examine the influence of spiritual leadership, perceived organizational support (POS), and affective commitment on OCB among hospital employees in Banjarbaru. The research applied an explanatory quantitative method with a sample of 100 respondents selected from a population of 184 using accidental sampling. Data were collected using a semantic differential scale (1–7) questionnaire and analyzed using Partial Least Square (PLS). The findings revealed: (1) spiritual leadership has a significant positive effect on OCB but not on affective commitment; (2) POS significantly influences affective commitment but has no significant effect on OCB; (3) affective commitment significantly influences OCB. These results indicate that while spiritual leadership and POS do not directly affect OCB through affective commitment, the latter plays a key mediating role in enhancing extra-role behaviors. This study contributes to the understanding of internal psychological and leadership factors that foster proactive work behaviors, and offers practical insights for developing human resource strategies in the healthcare sector.